2020
DOI: 10.1016/j.jmb.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Release of Human TFIIB from Actively Transcribing Complexes Is Triggered upon Synthesis of 7- and 9-nt RNAs

Abstract: RNA polymerase II (Pol II) and its general transcription factors assemble on the promoters of mRNA genes to form large macromolecular complexes that initiate transcription in a regulated manner. During early transcription these complexes undergo dynamic rearrangement and disassembly as Pol II moves away from the start site of transcription and transitions into elongation. One step in disassembly is the release of the general transcription factor TFIIB, although the mechanism of release and its relationship to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 38 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…The above result generally agrees with earlier biochemical studies that are not fully consistent with each other. For example, by detecting changes in the transcription bubble, complex stability, or dissociation of GTFs (mainly TFIIB), previous studies showed that the functional transition occurs when RNA reaches 7 ( 35 ), 8 ( 34 ), 9 ( 37 ), 10 ( 33 ), 7 or 9 ( 38 ), 12 or 13 ( 63 ), or more than 9 or 10 nt ( 36 , 57 ). This apparent discrepancy may result from the heterogeneity of transcription initiation, variations in promoters and experimental contexts, and limitations of the detection method (see supplementary text).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The above result generally agrees with earlier biochemical studies that are not fully consistent with each other. For example, by detecting changes in the transcription bubble, complex stability, or dissociation of GTFs (mainly TFIIB), previous studies showed that the functional transition occurs when RNA reaches 7 ( 35 ), 8 ( 34 ), 9 ( 37 ), 10 ( 33 ), 7 or 9 ( 38 ), 12 or 13 ( 63 ), or more than 9 or 10 nt ( 36 , 57 ). This apparent discrepancy may result from the heterogeneity of transcription initiation, variations in promoters and experimental contexts, and limitations of the detection method (see supplementary text).…”
Section: Resultsmentioning
confidence: 99%
“…5D). Moreover, TFIIB dissociates from Pol II before RNA reaches 10 nt in length ( 38 , 39 ). Previous studies in yeast Pol II have proposed that steric clashes between RNA and the B-ribbon may lead to TFIIB dissociation ( 44 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations